From vision to action (V2A): Advancing sustainable management of multifunctional landscapes in Akole, Maharashtra (India) - Barooah, Prapti; Falk, Thomas; Joshi, Rajashree; V. S., Viswadev; Krishnan, Smitha; Kumar, Gopal; Malaiappan, Sudharsan (International Food Policy Research Institute, 2025)
The Vision-to-Action (V2A) approach was developed to support inclusive stakeholder conversations to create a shared vision for a desirable future, develop holistic and medium-term transition pathways towards sustainable living landscapes, and define realistic, collectively agreed-upon concrete action plans that outline the behavior changes required to transition from their current situation to the envisioned future. It is designed to foster action that is multi-actor (e.g., producers, traders, enterprises, consumers, policymakers), multidimensional (e.g., agricultural, environmental, economic, social), and multi-scalar (e.g., farm, landscape, system) to realize sustainable food system transformation. This method structures conversations to allow stakeholders to discuss and agree about who, what, when and where to engage in the sought transformation processes. The V2A process and results also point to opportunities and entry points for responsive external support including by research-in-development partners such as the CGIAR Science Program on Multifunctional Landscapes.